2007
DOI: 10.1086/510078
|View full text |Cite
|
Sign up to set email alerts
|

Nevirapine Levels after Discontinuation of Rifampicin Therapy and 60‐Week Efficacy of Nevirapine‐Based Antiretroviral Therapy in HIV‐Infected Patients with Tuberculosis

Abstract: Seventy patients with human immunodeficiency virus (HIV) and tuberculosis coinfection who initiated nevirapine-based antiretroviral therapy and had trough nevirapine levels determined while receiving rifampicin were enrolled in a study. After discontinuation of rifampicin therapy, mean nevirapine levels (+/- standard deviation) increased from 5.4+/-3.5 mg/L to 6.4+/-3.4 mg/L (P=.047), but no nevirapine-related adverse events occurred. There was no statistically significant difference in 60-week antiviral effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 13 publications
4
23
1
Order By: Relevance
“…Two adequately powered Thai studies conducted in patients with TB reported reductions of nevirapine trough concentrations of 15.6% 18 and 37.2%, 8 which are similar to the 26.3% that we found. However, the mean trough nevirapine concentrations with concomitant rifampicin-based antitubercular therapy in the Thai studies were 5.5 and 5.4 mg/L, 8,18 considerably higher than the 3.2 mg/L that we found.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Two adequately powered Thai studies conducted in patients with TB reported reductions of nevirapine trough concentrations of 15.6% 18 and 37.2%, 8 which are similar to the 26.3% that we found. However, the mean trough nevirapine concentrations with concomitant rifampicin-based antitubercular therapy in the Thai studies were 5.5 and 5.4 mg/L, 8,18 considerably higher than the 3.2 mg/L that we found.…”
Section: Discussionsupporting
confidence: 84%
“…However, the mean trough nevirapine concentrations with concomitant rifampicin-based antitubercular therapy in the Thai studies were 5.5 and 5.4 mg/L, 8,18 considerably higher than the 3.2 mg/L that we found. The likely explanation for the higher nevirapine trough concentrations is their lower body weight (10 kg lower than our patients' mean weight of 65.8 kg), given that nevirapine clearance is similar in Thai and South African patients.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In another study on 70 Thai patients coinfected with HIV and TB, rifampicin reduced the nevirapine C min by 17%, but more than 70% of the patients had concentrations above 3.4 mg/L [13]. These patients were followed after the discontinuation of rifampicin, and their C min increased by 16.7% [14].…”
Section: Discussionmentioning
confidence: 98%
“…The mutation is observed after 4 weeks of monotherapy and may occur in just 2 weeks if viral replication is not well controlled in the presence of nevirapine [4]. Several reports on the effect of rifampicin on nevirapine pharmacokinetics have been published [4,[9][10][11][12][13][14]. However, to our knowledge this is the first modelling report on the effect of rifampicin on nevirapine pharmacokinetics in South African patients.…”
Section: Introductionmentioning
confidence: 99%